Chapter Use of RPAS to monitor coastal dune systems and beach erosion in Guardamar del Segura, Spain - Pagán, José Ignacio (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The complex dune ecosystem and beaches of Guardamar del Segura has proven to be an excellent test site for monitoring coastal processes using a small, lightweight, easily deployable and affordable commercial RPAS. The possibility of quickly obtaining orthophotos and Digital Surface Models of very high resolution, covering large extensions at a low cost, enables us to model and monitor these rapid-changing environments with regularity and accuracy.